Grating-based X-ray phase contrast for biomedical imaging applications - Pfeiffer, Franz; Herzen, Julia; Wiliner, Marian; Chabior, Michael; Auweter, Sigrid; Reiser, Maximilian; Bamberg, Fabian (Zeitschrift für Medizinische Physik, 2013)
In this review article we describe the development of grating-based X-ray phase-contrast imaging, with particular emphasis on potential biomedical applications of the technology. We review the basics of image formation in grating-based phase-contrast and dark-field radiography and present some exemplary multimodal radiography results obtained with laboratory X-ray sources. Furthermore, we discuss the theoretical concepts to extend grating-based multimodal radiography to quantitative transmission, phase-contrast, and dark-field scattering computed tomography. © 2013.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Grating interferometry; Phase-contrast tomography; X-ray imaging; X-ray phase contrast